Impact of factors share on productivity of ginger (Zingiber officinale) in NEHR of India - Singh, Ram; Chahal, V P; Feroze, S M; Kumar, Shiv (The Indian Journal of Agricultural Sciences, 2020)
The ginger crop being major crop in the region plays a vital role in livelihood and income of the farmers of the North Eastern Hill Region (NEHR). Study covered NEHR states except Assam. The data pertains to year 2017–18 containing sample size of 271 farmers. The results discussed ample scope to increase factor share to scale-up productivity of ginger. Among the different factors of ginger production, the ginger seed and human labour have contributed large share in ginger production. The study recommends for construction of post harvest storage structures for ginger rhizome in the locality of ginger growing area to store their rhizome for next season crop. To enhance research and development expenditures in North Eastern Hill Region was especially to develop small size of machinery with the intent to reduce cost of human labour. The potential of ginger crop in the study area needs to be tapped not only to enhance the factor share but also through technological interventions.